2012 IEEE International Conference on Robotics and Automation 2012
DOI: 10.1109/icra.2012.6224868
|View full text |Cite
|
Sign up to set email alerts
|

The vsaUT-II: A novel rotational variable stiffness actuator

Abstract: In this paper, the vsaUT-II, a novel rotational variable stiffness actuator, is presented. As the other designs in this class of actuation systems, the vsaUT-II is characterized by the property that the output stiffness can be changed independently of the output position. It consists of two internal elastic elements and two internal actuated degrees of freedom. The mechanical design of the vsaUT-II is such that the apparent output stiffness can be varied by changing the transmission ratio between the elastic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 17 publications
(30 reference statements)
0
55
0
3
Order By: Relevance
“…As is illustrated in Figure 8(c), the movable pulley rod (10) and the movable baffle (7) are used to ensure that the tendons always maintain contact with the driving pulley. The related design and kinematic relationship are shown in Figure 9.…”
Section: Mathematical Modelling Of the First Vsamentioning
confidence: 99%
See 1 more Smart Citation
“…As is illustrated in Figure 8(c), the movable pulley rod (10) and the movable baffle (7) are used to ensure that the tendons always maintain contact with the driving pulley. The related design and kinematic relationship are shown in Figure 9.…”
Section: Mathematical Modelling Of the First Vsamentioning
confidence: 99%
“…Some designs rely on changing the transmission ratio between the output and the internal elastic elements. The AwAS-II [5], CompAct-VSA [6], CompAct-ARS [7], HDAU [8], the vsaUT [9], the vsaUT-II [10], and the mVSA-UT [11] use a lever arm of variable effective length to regulate the transmission ratio. As is elaborated in [12], the output stiffness of these variable stiffness actuators can be changed without any energy injection into or extraction from the internal elastic elements.…”
Section: Introductionmentioning
confidence: 99%
“…두 개의 모터가 비 선형성의 탄성요소로 연결되어 장력을 조절하는 방식을 채택한 MACCEPA, (6) VSA-II (7) 및 VSAJoint, (2) 판 스프링을 활용한 VSJ, (8) 가변 모멘트 팔 기반의 HDAU, (9) AwAS, (10) AwAS-II (11) 및 vsaUT-II (12) …”
unclassified
“…Examples include robotic hands, where the elastic elements are used to perform a stable grasp [1][2][3], flying robots, in order to estimate the pitch torques generated by wings during flapping [4] and robotic snakes, for estimating ground contact forces [5]. Furthermore elastic elements are key components of Series Elastic Actuators (SEAs) [6][7][8][9], Variable Stiffness Actuators (VSAs) [10][11][12][13][14][15][16][17][18] and, more generally, of Variable Impedance Actuators (VIAs) [19], where damping can also be adjusted by properly controlling the device. In this field, a seminal work is that of Fasse et al [20], where an electromagnetic variable impedance actuator is demonstrated, capable of exerting a torque much higher than that of the prototype described in this paper.…”
Section: Introductionmentioning
confidence: 99%